The Impact Of Implementing A Unified Medical Records System On Enhancing The Continuity Of Emergency Care Between Ambulance Teams And Hospitals (The Review of Diabetic Studies, 2025)
This study aimed to identify the lack of implementation of a unified medical records system in the social security system, as well as the lack of protection between patient teams and hospitals in the Kingdom of Saudi Arabia. To begin the basic study of descriptive analysis, a standardized questionnaire was used to survey data retrieved from (200) participants from the cadres working in the bicycle and emergency sector, to show paramedics, doctors and nurses. The questionnaire consisted of ten items with multiple dimensions such as: integrated information, speed and accuracy of access to data exchange, limiting the cause, and the necessity of medical integration. The overall overall score of the Bulgarian responses (4.03) was declared high, which contributed to the system's success in improving the quality and continuity of health care. Speed and accuracy of data access” came in first with an average of (4.19), followed by “efficiency of information exchange” with an average of (4.07), while “limiting the reason for having a medical party” had the lowest average (3.90) while remaining within the collective level. The results of the t-test also showed no statistically significant differences between workers in patient and hospital teams (Sig = 0.364), as well as no differences attributable to the diversity of years of experience based on one-way analysis of variance (Sig = 0.338) These results indicate that a unified medical records system is effective in all work environments with no significant differences. The study recommended the widespread application of the system, the intensification of training and qualification programmes, and emphasised the sustainability of the outstanding technical and communication effectiveness.